A Short Review of Cybersecurity Issues and Efforts in the Water Industry - Jamil N.; Che Cob Z.; Abdul Rahim F.; Mohd Sidek L.; Basri H.; Sharizan Sharizal N.I.I. (Springer Science and Business Media Deutschland GmbH, 2024)
As water infrastructure becomes increasingly connected, it is also becoming more vulnerable to cyber-attacks. In this paper, we review real-world examples of cyber-attacks on water systems, highlighting the potential risks and threats faced by the water sector. To better understand the vulnerabilities of water systems to cyber-attack, we develop an architecture of the water system and analyze the potential risks and threats at each layer of the architecture. We then recommend security requirements for each layer to enhance the overall security of the water system. We also review the existing international standards and initiatives related to securing the water sector. Our research shows that securing water systems against cyber threats requires a comprehensive approach that considers both technical and organizational measures. This paper contributes to the growing body of literature on water security and provides a valuable resource for policymakers and practitioners to improve and enhance the security and resilience of water systems against cyber threats. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.